Glutathione S-Transferases M1 and P1 Prevent Aggravation of Allergic Responses by Secondhand Smoke - Gilliland, Frank D; Li, Yu-Fen; Gong, Henry, Jr; Diaz-Sanchez, David (American journal of respiratory and critical care medicine, 2006)
Secondhand tobacco smoke (SHS) and traffic-related air pollutants are associated with asthma and allergy. Diesel exhaust particles (DEPs) and SHS can interact with allergens in exacerbating allergic airway diseases through generation of reactive oxygen species. Glutathione S-transferases (GSTs) metabolize reactive oxygen species and detoxify electrophilic xenobiotics present in SHS and DEPs. We tested the hypotheses that functional GSTM1-null genotype and GSTP1 codon 105 variants (Ile105 and Val105) are determinants of allergic responses to SHS, and that responses to SHS and DEPs are correlated. In a randomized, placebo-controlled crossover trial, 19 ragweed allergen-sensitive subjects who had previously participated in a DEP trial were challenged intranasally with allergen after having been exposed to either clean air or SHS at separate visits. Nasal allergen-specific IgE, histamine, IL-4, and IFN-gamma levels were measured before and after allergen challenge. Individuals with GSTM1-null or GSTP1 Ile105 genotypes showed larger nasal responses to allergens with SHS compared with clean air. GSTM1-null subjects had a larger increase in IgE than GSTM1-present subjects (median, 173.3 vs. 46.7 U/ml; p = 0.03), and the Ile105 GSTP1 genotype subjects had increased histamine (median, 10.2 vs. 4.6 nM; p = 0.01) after SHS plus allergen challenge. Responses to SHS and DEPs were correlated. Enhancement of IgE and histamine was greatest in the subjects with both the GSTM1-null and GSTP1 Ile/Ile genotypes. GSTM1 and GSTP1 are important cytoprotective factors that reduce SHS and DEP exacerbation of allergic responses.